Obstetrical outcomes and biomarkers to assess exposure to phthalates: A review. (October 2015) - Marie, Cécile; Vendittelli, Françoise; Sauvant-Rochat, Marie-Pierre
Abstract: Studies of the effects on pregnancy outcomes of in utero exposure to phthalates, contaminants that are widely present in the environment, have yielded conflicting results. In addition, the mode of assessment of exposure varies between studies. The aim of this review was therefore to establish a current state of knowledge of the phthalates and metabolites involved in unfavorable pregnancy outcomes. Extant data were analyzed to determine which biomarker is the best suited to assess the relation between in utero exposure to phthalates and pregnancy outcomes. This review of the literature was conducted using the database of PubMed. A search was made of studies investigating exposure to phthalates and the following birth outcomes: preterm birth (gestational age < 37 weeks), change in gestational age, change in body size at birth (birth weight, length, head circumference), anti-androgenic function, decreased anogenital distance, cryptorchidism, hypospadias and congenital malformation. The methodological approach adopted in each study was examined, in particular the methods used for exposure assessment (biomarkers and/or questionnaire). Thirty-five studies were included. Premature birth and decreased anogenital distance were the most commonly reported outcomes resulting from a moderate level of exposure to phthalates. The principal metabolites detected and involved were primary metabolites of di-2(ethylhexyl)-phthalate (DEHP) and di- n -butyl-phthalate (DnBP). No clear conclusion could be drawn with regard to gestational age at birth, body size at birth and congenital malformations. In epidemiological studies, maternal urine is the most suitable matrix to assess the association between in utero exposure to phthalates and pregnancy outcomes: in contrast to other matrices (cord blood, amniotic fluid, meconium and milk), sampling is easy, non-invasive and, can be repeated to assess exposure throughout pregnancy. Oxidative metabolites are the most relevant biomarkers since they are not prone to external contamination. Further epidemiological studies are required during pregnancy to i) determine the role of phthalates other than DEHP [currently replaced by various substitution products, in particular diisononyl-phthalate (DiNP)]; ii) establish the effect of phthalates on other outcomes (body size adjusted for gestational age, and congenital malformations); iii) determine the pathophysiological pathways; and iv) identify the most suitable time for biomarker determination of in utero exposure to phthalates. Highlights: Epidemiological data about in utero exposure to phthalates and pregnancy outcomes Preterm birth and decreased anogenital distance are the most reported outcomes. Primary metabolites of DEHP and DnBP are the most frequently metabolites involved. Secondary metabolites in maternal urine are the most suitable biomarkers. Further studies are required to clarify the role of phthalates other than DEHP and their mode of action.